Configuración, interpretación y aplicación de las normas penales en blanco en la legislación penal cubana - Alarcón Borges, Ramón (2023)
The project leaves of the non - existence in the Cuban doctrine of theoretical budgets that they serve from sustena nce to an appropriate formulation, interpretation and application of the penal types configured as penal norms in white that it transcends to the affectation of the principles of legality and juridical security. With the investigation it is possible to ske tch the theoretical budgets that sustain the configuration of the penal norms in white, under a prism of doctrinal, historical analysis, exegetical and compared, according to the new tendencies of the Penal Law, leaving of the I diagnose of the main proble ms in the juridical penal norms, configured as penal norms in white in Cuba, as well as in their interpretation and application.